2017
DOI: 10.1007/s00382-017-3736-4
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of CORDEX-Arctic daily precipitation and temperature-based climate indices over Canadian Arctic land areas

Abstract: the use of reanalyses as reference datasets for the evaluation of RCM mean air temperature and hot extremes over northern Canada, but not for cold extremes and precipitation indices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
44
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(47 citation statements)
references
References 87 publications
3
44
0
Order By: Relevance
“…High values of similarity metrics such as correlation coefficients or NSE do not necessarily imply high distributional or temporal structure similarity (Mo et al, ). The results here are consistent with the general findings of Wong et al () and Diaconescu et al (); however, the graphical techniques presented provide additional insight into the shortcomings of gridded datasets that may not be evident in statistical performance measures (Crout et al, ). For example, in MERRA‐2 T max (Figure c), there is a clear discontinuity where the gridded temperatures are near 0°C.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…High values of similarity metrics such as correlation coefficients or NSE do not necessarily imply high distributional or temporal structure similarity (Mo et al, ). The results here are consistent with the general findings of Wong et al () and Diaconescu et al (); however, the graphical techniques presented provide additional insight into the shortcomings of gridded datasets that may not be evident in statistical performance measures (Crout et al, ). For example, in MERRA‐2 T max (Figure c), there is a clear discontinuity where the gridded temperatures are near 0°C.…”
Section: Discussionsupporting
confidence: 91%
“…Gridded hydrometerological products (gridded datasets) can be a complement to the existing sparse data network. Gridded datasets have been used to characterize the variability and trends of hydroclimate systems where observations are sparse or do not exist (e.g., Snauffer, Hsieh, & Cannon, ; Way, Oliva, & Viau, ; Woo & Rouse, ), to assess the outputs of global and regional climate models (e.g., Diaconescu, Mailhot, Brown, & Chaumont, ; Field, Barros, Stocker, & Dahe, ), and to study hydro‐ecological responses to changing climate (e.g., Price et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Inuit exposure, sensitivity and adaptive capacity to climate change Inuit exposure to climate change In the exposure layer, extreme weather has the largest degree centrality (C D =27, figure 4, table 3) and would therefore affect many variables within the Inuit vulnerability system. Temperature is the second most central variable (C D =24) and is expected to increase with climate change, leaving the region more prone to disasters such as floods (C D =24) or storm surges (C D =20) [51,52]. Combining quantitative metrics with qualitative systems understanding can help parameterize a vulnerability model.…”
Section: Resultsmentioning
confidence: 99%
“…Here we use highresolution regional climate model simulations and it has been shown that regional climate model simulations provide more realistic information of precipitation, with intensities and frequencies comparable to the recorded station data (Chan et al, 2013), than global climate models. To make a direct comparison between station data and model simulations, some studies remap the gauge measurements onto a regular grid similar to the simulations (Diaconescu et al, 2016), some interpolate the model grid points to the gauge locations (Xie et al, 2019), and some directly choose the grid points closest to the stations (Diaconescu et al, 2018;Pendergrass and Knutti, 2018). Here we choose the simplest way, in that we selected the closest grid point to compare with station observations.…”
Section: Methodsmentioning
confidence: 99%